2003
DOI: 10.1152/ajpcell.00518.2002
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin-independent regulation of plasma membrane Ca2+ ATPase-4 in the vascular smooth muscle cell cycle

Abstract: . Calcineurinindependent regulation of plasma membrane Ca 2ϩ ATPase-4 in the vascular smooth muscle cell cycle. Am J Physiol Cell Physiol 285: C88-C95, 2003; 10.1152/ajpcell.00518.2002.-Calcineurin mediates repression of plasma membrane Ca 2ϩ -ATPase-4 (PMCA4) expression in neurons, whereas c-Myb is known to repress PMCA1 expression in vascular smooth muscle cells (VSMC). Here, we describe a novel mouse VSMC line (MOVAS) in which 45 Ca efflux rates decreased 50%, fura 2-AM-based intracellular Ca 2ϩ concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 51 publications
3
37
0
Order By: Relevance
“…ATP2B1 regulates the homeostasis of cellular calcium ion levels, which is important in controlling vascular smooth muscle contraction and dilation. 13,14 However, it has been difficult to speculate the exact role of ATP2B1 in physiology because of the large number of isoforms and the multiplicity of interacting molecules. 15 Related to its role in blood pressure, it is not clear yet whether ATP2B1 directly regulates the contraction and dilation of vascular smooth muscle by pumping out intracellular Ca ++ or it indirectly regulates the blood pressure by transmitting signals from vascular endothelial cells into the vascular smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…ATP2B1 regulates the homeostasis of cellular calcium ion levels, which is important in controlling vascular smooth muscle contraction and dilation. 13,14 However, it has been difficult to speculate the exact role of ATP2B1 in physiology because of the large number of isoforms and the multiplicity of interacting molecules. 15 Related to its role in blood pressure, it is not clear yet whether ATP2B1 directly regulates the contraction and dilation of vascular smooth muscle by pumping out intracellular Ca ++ or it indirectly regulates the blood pressure by transmitting signals from vascular endothelial cells into the vascular smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…The biological function of ATP2B1 involves the homeostasis of cellular calcium ion levels, which is known to control vascular smooth muscle contraction and dilation. 14,15 The SNP rs1378942 is located in the first intron of CSK (c-src tyrosine kinase) at chromosome position 15q23-25. Our results showed that rs1378942 is associated with SBP in both cohorts (meta-analysis, P ¼ 1.34 Â 10 À5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Splenocytes were cultured as described above to induce TNF␣ expression. Supernatants were harvested and transferred to a smooth muscle cell line (Movas [21]), which was seeded 18 hours previously (0.25 ϫ 10 6 cells/well, 24-well plate). In separate experiments, preseeded Movas cells were left untreated or were treated with 20 ng/ml recombinant TNF␣ (eBiosciences) or recombinant TNF␣ plus various concentrations of drugs.…”
Section: Methodsmentioning
confidence: 99%